Mechanical Parameters and Post-Cracking Behaviour of HPFRC according to Three-Point and Four-Point Bending Test - Francesco Bencardino (Advances in Civil Engineering)
High performance fibre reinforced concrete (HPFRC) is a modern structural material with a high potential and with an increasing number of structural applications. Structural design of HPFRC elements is based on the post-cracking residual strength provided by fibre reinforcement, and for structural use, a minimum mechanical performance of HPFRC must be guaranteed. To optimize the performance of HPFRC in structural members, it is necessary to establish the mechanical properties and the post-cracking and fracture behaviour in a univocal and reliable way. The best test methodology to evaluate the post-cracking and toughness properties of HPFRC is the beam bending test. Two different types of configurations are proposed: the three-point and the four-point bending tests. The overall focus of this paper is to evaluate the mechanical properties and the post-cracking and fracture behaviour of HPFRC, using the two different standard test procedures. To achieve these aims, plain and fibre concrete specimens were tested. All the test specimens were extensively instrumented to establish the strength properties, crack tip and crack mouth opening displacement, and post-cracking behaviour. The results of the two types of bending tests were critically analysed and compared to identify and highlight the differing effects of the bending load configurations on the mechanical parameters of HPFRC material.